KONVERSI KULIT PISANG MENJADI GLUKOSAMENGGUNAKAN KATALIS ARANG AKTIF TERSULFONASI - Riskatama Atmaji; Zulfikar Muriadiputra; Didi Dwi Anggoro (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2013)
This research engages banana peel as the source of cellulose for hydrolysis into glucose using sulfonated activated carbon as catalyst. The aims of this research are to study the effect of hydrolysis temperature, hydrolysis times, and the weight of catalyst, to conclude the mathematical model plotted from the yield and the variables, and to conclude The optimum conditions for hydrolysis of banana peel cellulose into glucose which includes hydrolysis temperature, hydrolysis times, and the weight of catalyst. This research is designed into two steps, the sulfonation of the activated carbon and the hydrolysis of banana peel cellulose. H2SO4 10 N is used for the sulfonation which is done in 6 hours at 40oC. After the catalysts are dried and calcinated, the catalysts are ready for the hydrolysis precesses which are done in the autoclave batch reactor. After that, spectrophotometer is used to analyze the sample. The results was plotted on a mathematical model and then optimized using the software Statistica 6.0 by Response Surface Methodology method (RSM). The result obtained by a mathematical model for relationship activator combination temperature, time and weight of catalyst for content glucose Y = 3,035+0,18 x1 + 0,04 x1² + 0,089 x2 + 0,012 x2² +0,047x3 – 0,021 x3² – 0,014 x1x2 – 0,087 x1x3 + 0,022 x2x3. The optimum conditions of hydrolysis variable for glucose obtained by statistica 6.0 software which the graph fitted response surface and contour plot indicates the optimum hydrolysis temperature is in the range 112°C to 115°C, the optimum hydrolysis time is in the range 300 minutes to 500 minutes, and the optimum weight of catalyst is about 30 gr which the sample contains 3,6 mg/ml of glucose.